Electricity Provision and Tax Mobilization in Africa - Blimpo, Moussa (World Bank, Washington, DC, 2018)
This paper provides evidence on how the provision of social infrastructure, such as reliable electricity, can be leveraged to increase taxation in developing countries, particularly in Sub-Saharan Africa. First, using comprehensive data from the latest round of the Afrobarometer survey, the paper uses the instrumental variable approach to estimate the effect of access to and reliability of electricity on the tax compliance attitudes of citizens in 36 countries in Sub-Saharan Africa. The evidence shows a significant positive effect of electrification on tax compliance attitudes, with potentially strong externalities. The analysis also finds that the reliability of supply is crucial in explaining the impact of electricity access on attitudes toward taxes. Second, the paper provides suggestive evidence on national identity as one channel driving this impact. Access to social amenities such as electricity induces a sense of national identity among citizens, thereby incentivizing them to contribute, through taxes, toward the functioning of the state. Third, using data from the most recent World Bank Enterprise Surveys and under conservative assumptions, the paper estimates that countries in the region could in total generate additional tax revenues of more than $9.5 billion (4.3 percent of total tax revenue) per year solely by resolving issues related to electricity shortages. Put together, the paper concludes that the financial returns associated with public investments toward improving access to and reliability of electricity are substantial and could be harnessed to augment the financing gap in the sector.